A Scalar Measure of Acoustic Hazard Assessment - BATKO, Wojciech; RADZISZEWSKI, Leszek; BĄKOWSKI, Andrzej (Archives of Acoustics, 2024)
The article addresses the problem of assessing the impact of road modernization on improving the acoustic environment. It formulates a hypothesis about the advisability of adopting the scalar dimension of the decibel space to describe acoustic hazards. It is proposed to reduce the analysis of changes in sound levels to the analysis of changes in the coefficient of exceedance of the recommended noise levels. Its value is determined by the decibel relation of dividing sound levels. The basis for the assessment of the effectiveness of the adopted solution was the analysis of the statistical characteristics of monitored exceedances of recommended noise levels, considered through the prism of the current and proposed measure. They showed greater sensitivity of the proposed coefficient in the assessment of the improvement of the acoustic climate caused by road modernization. For example, the median noise level for nights before the road modernization was 66.9 dB(A), and after the modernization 65.6 dB(A). However, the coefficient of exceedances decreased by approximately 25 %. Numerical simulations, in accordance with the Cnossos noise model, showed that reducing the speed by 10 km/h will reduce the coefficient of exceedances by approximately 20 %.